MEKANISME PASAR ISLAMI DALAM TEORI EKONOMI ISLAM - Muhammad Dhiyaudin; Yayat Sujatna (Universitas Dharmawangsa, 2025)
This paper investigates the mechanisms of Islamic markets as conceptualized within Islamic economic theory, highlighting the fundamental principles that set them apart from conventional market systems. It emphasizes the importance of ethical conduct, justice, and transparency, which are core tenets of Islamic teachings. Key principles such as mutual consent (Ar-Ridha), fairness in transactions, and the prohibition of exploitative practices like usury (riba) and hoarding (ikhtikar) are explored to illustrate how they influence market dynamics. The study further analyzes the role of supply and demand in determining prices within Islamic markets, demonstrating how these principles contribute to establishing a fair and equitable trading environment. Additionally, the contributions of notable Islamic scholars, including Al-Ghazali and Ibn Khaldun, are examined to provide a historical perspective on the evolution of these concepts. The paper also addresses contemporary challenges in applying Islamic market mechanisms in today’s global economy, such as unethical business practices and market distortions that contradict Islamic values. By offering insights into the integration of Islamic principles into modern economic practices, this research aims to foster a more just and equitable economic landscape that aligns with the ethical foundations of Islam.